An Econometric Analysis of the Operating Profit of Romanian Companies - Adriana Deaconu (Journal of Accounting and Management Information Systems (JAMIS), 2011)
This paper aims to contribute to the empirical literature by employing a panel data model for analysing the connection between operating profit of Romanian companies and the turnover, tangible assets, payrolls, stocks and cash. We find that the companies with a higher turnover recorded better economic results and an increased payroll is associated with a decline in economic performance. Likewise, companies that have the cash and / or tangible assets registered superior performance, while growth in stocks is accompanied by lower economic performance of the companies. Sectorial data confirm these results.
Keywords: C23; D24; L25; 650; panel data model; operating profit; turnover; tangible assets; payrolls; stocks and cash